ANALISIS DEFORMASI PERMUKAAN MENGGUNAKAN METODE DInSAR (Differential Interferometry Synthetic Aperture Radar) PADA STUDI KASUS GEMPABUMI LOMBOK PERIODE AGUSTUS 2018 - Muhammad Fikri Azhari; Karyanto Karyanto; Syamsurijal Rasimeng; Bagus Sapto Mulyanto (Engineering Faculty Universitas Lampung, 2020)
Lombok is located on the boundary of active tectonic plates, this is what caused the Lombok Earthquake on August, 2018. DInSAR is a remote sensing technology that utilizes radar satellites to measure the amount of deformation on the surface of the ground with sub-centimeter accuracy. This study aims to obtain the value of surface deformation after the earthquake that struck the Lombok region, in August 5, 2018 Earthquake and the August 19 2018 Earthquake and analyze impact and charateristics of the deformation that occurred in the two earthquakes. The research was carried out based on SAR Sentinel-1 image processing using SNAP Software, Google Earth and ArcGIS 10.3. Deformation that occurred after the Lombok earthquake on August 5, 2018 caused an increase in land level (uplift) on the coast of North Lombok with a deformation value of 15-30 cm to the Line of Sight (LOS). Whereas deformation in the form of subsidence occurs in the City of Mataram and West Lombok with a value of -6 to -16 cm to the Line of Sight (LOS). While the deformation that occurred after the Lombok earthquake on August 19, 2018, caused an increase in land level (uplift) on the East Lombok coast with a deformation value of 18 to 31 cm to the Line of Sight (LOS). Whereas deformation in the form of subsidence occurs in Central Lombok with a value of -3 to -17 cm to the Line of Sight (LOS).